Особенности информационного подхода в теории механизмов и машин - Луцкий, С. В. (НТУ "ХПИ", 2007)
The considered features of use of the basic situations of the information approach at the decision of tasks and dynamic analysis of mechanisms. The entered concepts of information balance, basic property of information process, and ассошгі of quantity of the information of physical sizes.
Keywords: механика машин; теория механизмов; теория машин; информационный подход; абсолютная погрешность; интегрированные машиностроительные производства